2008
DOI: 10.1021/jp7107544
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Uptake of NO3, N2O5, NO2, HNO3, and O3on Three Types of Polycyclic Aromatic Hydrocarbon Surfaces

Abstract: We investigated the reactive uptake of NO3, N2O5, NO2, HNO3, and O3 on three types of solid polycyclic aromatic hydrocarbons (PAHs) using a coated wall flow tube reactor coupled to a chemical ionization mass spectrometer. The PAH surfaces studied were the 4-ring systems pyrene, benz[a]anthracene, and fluoranthene. Reaction of NO3 radicals with all three PAHs was observed to be very fast with the reactive uptake coefficient, gamma, ranging from 0.059 (+0.11/-0.049) for benz[a]anthracene at 273 K to 0.79 (+0.21/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
150
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(155 citation statements)
references
References 51 publications
5
150
0
Order By: Relevance
“…According to eq 3, the uptake coefficients for NO 3 radicals on BaA, Ch, Py, 1-NP, and 1-OHP particles are 2.4, 1.5, 3.1, 0.5, and 4.8, respectively, which are much larger than the reported data. 12,27 Lambe et al 44 reported that evaporation followed by gas-phase oxidation was the main reason resulting in the uptake coefficients greater than unity observed in their experiment. In this experiment, the vapor pressures of the 4-ring PAHs are less than 6 × 10 −4 Pa and their gas-phase reaction rates with NO 3 radicals are on the order of 10 −17 − 10 −16 cm 3 ·molecule −1 ·s −1 .…”
Section: ■ Results and Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…According to eq 3, the uptake coefficients for NO 3 radicals on BaA, Ch, Py, 1-NP, and 1-OHP particles are 2.4, 1.5, 3.1, 0.5, and 4.8, respectively, which are much larger than the reported data. 12,27 Lambe et al 44 reported that evaporation followed by gas-phase oxidation was the main reason resulting in the uptake coefficients greater than unity observed in their experiment. In this experiment, the vapor pressures of the 4-ring PAHs are less than 6 × 10 −4 Pa and their gas-phase reaction rates with NO 3 radicals are on the order of 10 −17 − 10 −16 cm 3 ·molecule −1 ·s −1 .…”
Section: ■ Results and Discussionmentioning
confidence: 87%
“…12 Considering that the maximum acquisition time of the kinetic data in the experiment is less than 300 s, the direct loss of PAH aerosols due to the reaction with NO 2 is neglected in this study. Kamens et al 35 have reported that the heterogeneous rate constants for reactions of PAHs with N 2 O 5 (∼2.5 × 10 14 molecules·cm −3 ) are on the order of 10 −18 cm 3 ·molecule −1 ·s −1 .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PAH nitroderivatives also cause concern for their direct mutagenicity. In addition to direct emission [9][10][11] , some nitro-PAHs are formed in the atmospheric liquid and gas phases via photochemical and dark nitration [12][13][14] . Concerning the inorganic composition of the atmospheric aqueous phase, halides (mainly chloride) are among the most abundant water-soluble anions.…”
Section: Introductionmentioning
confidence: 99%
“…1,27,31,33 Alternatively, some recent studies suggested that high concentrations of N 2 O 5 and NO 2 in the ambient atmosphere may block the accommodation and reaction of the NO 3 radical on the particle surfaces. 27,30,36 Unfortunately, these speculations have not yet been scientifically proven.…”
Section: ■ Introductionmentioning
confidence: 99%